HUBUNGAN ANTARA BUDAYA ORGANISASI DAN TINGKAT KEPERCAYAAN PADA PERUSAHAAN KONTRAKTOR DI SURABAYA - Wibowo, Lukas Hari; Andi, Andi (Magister Teknik Sipil Universitas Kristen Petra, 2014)
ABSTRACT: Construction business competition in Surabaya is getting tougher and thus require good performance in a construction organization. Performance of the organization requires trust that each individual, team, or group can act achieve the desired goal. The level of trust in an organization is influenced by the organizational culture. This study aims to determine the organizational culture and the level of confidence in large and medium-sized construction company in Surabaya, as well as the relationship between the level of trust and organizational culture.Based on the research that has been done, large and medium-sized contraction company in Surabaya tend to Clan culture type than other type of culture (Adhocracy, Market, and Hierarchy), which is concerned with loyalty and tradition; with high degree of organization trust in contractor company. Organizational culture is positively correlated with the level of trust, making any type of organizational culture as an important asset for the company to increase trust in the contractor organization, and the Hierarchy culture that can be used as the primary reference organization in increasing trust.